MEWUJUDKAN KEMITRAAN PUBLIK-SWASTA DALAM PEMBERIAN LAYANAN PENDIDIKAN DI KOTA TASIKMALAYA - Dewi, Maya Puspita (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The aim of this study is to examine the perspectives of stakeholder on the adoption of public-private partnership (PPP) policies on the provision of education services and challenges to their implementation. This study used a qualitative approach, and in-depth interview techniques were conducted on 8 (eight) informants selected purposively, including the Regional Secretary of the City of Tasikmalaya, the Head of the Tasikmalaya City Education Office, the Principal, Private Companies, Non-Government Organizations, and School Committees, who have a direct or indirect role with PPP policy. The results of this study indicate that stakeholder perception is still very limited regarding the concept of PPP and the absence of regulation regarding PPP is an inhibiting factor. The findings in this study are political commitment is the key for providing education services.